Implementasi Smart Village: Peningkatan Tata Kelola dan Keamanan Lingkungan Melalui Sistem IoT dan Asisten AI di Desa Kedungwaringin - Agus Sofwan; Riadi Marta Dinata; Kun Wardana; M. Febriansyah; Fivit Marwita; M. Ikrar; Niko Purnomo (Jurnal Pengabdian Tri Bhakti, 2026)
Village governments face dual challenges in the digital era: the demand for efficient public services and environmental security issues. In Kedungwaringin Village, these problems manifested as manual information services and the presence of unmonitored illegal dumping sites. This community service activity aimed to implement practical Smart Village solutions to improve village governance and environmental security through the application of appropriate technology. The method employed a quasi-experimental one-group pretest-posttest design involving education, live demonstrations, and hands-on training for the implementation of two key technologies: a solar-powered Internet of Things (IoT)-based environmental monitoring system, and a WhatsApp-based AI Assistant for information services. The results demonstrated a statistically significant increase in participant understanding (p < 0.05), with the 'Good' comprehension category rising from 8% to 32%. Furthermore, the activity successfully produced two functional, ready-to-use outputs that received a highly positive response from participants for being practical and relevant. Thus, the application of integrated IoT and AI technologies accessed via familiar platforms proved effective in accelerating digital transformation at the village level and can serve as a replicable pilot model